Takaful reporting on IFSB requirements in Malaysia: users and preparers perspective - Alias, Ahmad Zoolhelmi; Sulaiman, Maliah; Mohd Ariffin, Noraini; Abu Bakar, Intan Suryani (Human Resource Management Academic Research Society, 2023)
Bank Negara Malaysia (2014) mentioned the importance of having meaningful disclosure to protect participants. However, it did not provide details of the elements of meaningful disclosure. There is no specific guidelines or standards of what should be reported and how detailed the items should be reported. Takaful operators have more knowledge in the operational aspect of takaful, compared to the participants. Authorities try to harmonise all the possible variations and gaps between takaful operators (preparers) and participants (users) for the benefit of the industry. Any gap between what is expected to be reported (desirable) and what is actually reported needs to be analysed in order to provide more information relevant to the users and to standardise the disclosure level. By adopting Sulaiman’s (2005) framework, the study determines what users and preparers perceive as meaningful disclosure on the Islamic Financial Services Board (IFSB) standards. The first two objectives of the study are to determine the disclosure perspectives of the two parties while the third objective is to examine if gaps exist between the two stakeholders. Questionnaire was distributed to takaful agents to examine their perception while content analysis was employed to evaluate the actual level of disclosure in takaful operators' websites. The gap analysis was conducted between the desired and actual level of disclosure and found significant differences among all the gaps. Additionally, the average level of disclosure is 44%. It is hoped that the findings will assist authorities in formulating guideline in takaful industry in Malaysia.